PERCEIVED BENEFITS AND MAKING A CAREER CHOICE IN THE HOSPITALITY INDUSTRY: IS IT WORTH IT? - Adhoch, Ruth Yunia (ITB Journal Publisher, LPPM ITB, 2019)
Over the years, the university has graduated students in the Hotel and Hospitality (H&H) fields. However, existing statistics reveal that the majority of these graduates are not looking for work in the hotel industry or starting a business in their field of study. This paper discusses the findings of a study that seeks to establish demographic factors that influence the attitudes of undergraduate hotels and hospitality students towards career choices in the industry. The study was conducted at Moi University, Hotel and Hospitality Management Department, Uasin Gishu District, and the Department of Ecotourism, Hotel and Institutional Management of Maseno University (ECOHIM) in Kisumu District and used a sample of 145 respondents. Data were collected using a questionnaire and interview schedule and analyzed using SPSS ver. 25. The results of the study suggest that perceived benefits have a positive and significant effect on students' career choices in the industry (? = 0.013, ? <0.05). As a result, this paper argues that personal interests play an important role in attitude formation. Most students see this industry as having a reputation and have no qualms about working in it. However, it was noted that there were students who were less interested and had negative attitudes about the industry. This paper thus recommends that attention be given to these students through career guidance and counseling. Educators must communicate the benefits of working in the industry and the possibility of a career in the hospitality industry and companies to students. They must make them aware of the development of mobility, diversity of jobs in industry and other career information to create greater student interest in careers in the industry. Indeed, knowledge of career identity and long-term career planning will better enable students to build realistic and suitable career expectations.